Timely Diagnosis of Histoplasmosis in Non-endemic Countries: A Laboratory Challenge - Buitrago, María José; Martín-Gómez, M. Teresa (Frontiers in Microbiology, 2020)
Human histoplasmosis is a fungal infection caused by inhalation of microconidia of varieties capsulatum and duboisii of the thermally dimorphic fungi Histoplasma capsulatum. Although autochthonous cases of histoplasmosis have been diagnosed in almost every country, it is considered an endemic infection in specific areas of the world, many of which are popular travel destinations or the source of migratory movements. In non-endemic countries, the vast majority of the registered cases are imported and correspond to people having been exposed to the fungus in endemic locations as immigrants, expatriates, transient workers or tourists, with sporadic reported cases associated to organ donation. Misdiagnosis and delays in initiation of treatment are not uncommon in cross-border infections, and they are associated with high fatality-rates specially in patients with compromised cellular immunity in which progressive disseminated forms develop. In fact, the diagnosis of this infection in non-endemic countries is hampered by lack of clinical suspicion and paucity of diagnostic tools that can offer rapid and accurate results. Assays based on nucleic-acid amplification present as a suitable alternative in this situation, offering improved sensitivity and specificity, shortened turnaround time, and increased biosafety by avoiding culture manipulation. In non-endemic regions, molecular techniques are being used mainly in laboratories from countries that have registered an increase in the incidence of imported cases, although the number of published techniques is limited and consensus is lacking. Efforts are currently underway to standardize nucleic acid amplification-based techniques for its implementation in areas registering a rising number of imported cases.